Family History and Smoking as Key Predictors of Obesity among Young Adults in Latin America: A Secondary Data Analysis - Utami, Nurul Putrie; Pranolo, Andri (Majalah Kesehatan Indonesia, 2025)
The prevalence of obesity continues to increase in various countries. Obesity is a multifactorial condition influenced by lifestyle, diet, and genetic factors. This study aims to identify risk factors associated with obesity using secondary data analysis conducted using the Obesity Dataset, which consists of 485 individuals aged 14–61 years from Mexico, Peru, and Colombia. The research data were tested using the chi-square test to assess the relationship between obesity risk factors, followed by a multivariate test using logistic regression. The results indicated that a significant relationship with obesity was only found in the factors of a family history of obesity, smoking status, and age group. Individuals with a family history of overweight were almost five times more likely to be obese (OR = 4.98; 95% CI: 2.25–11.04; p < 0.001). Smokers had nearly three times higher odds of obesity compared to non-smokers (OR = 2.91; 95% CI: 1.17–7.24; p = 0.022). In addition, older age was associated with an increased likelihood of obesity (OR = 4.84; 95% CI: 1.51–15.49; p = 0.008). These findings conclude that genetic factors and smoking habits have a stronger association with obesity than dietary factors and physical activity. This study suggests that public health interventions should encompass not only diet and physical activity but also incorporate smoking prevention and cessation programs as essential components of obesity control strategies. Futhermore, population with family history of overweight and older age need to optimize prevention and nutritional intervention efforts to prevent and overcome obesity.